Size Effect of Concrete Specimens on the Acoustic Emission Characteristics under Uniaxial Compression Conditions. (2nd October 2017) - Wu, Jianbo; Wang, Enyuan; Ren, Xuekun; Zhang, Mingwei
Abstract : Acoustic emission (AE) experiments under uniaxial compression and cyclic loading-unloading compression conditions were performed using different sizes of cubic concrete specimens. The influences of the loading methods and the concrete sizes on the mechanical parameters and the concrete AE activities were analyzed. The loading method was found to have great impact on the deformation, failure, and energy dissipation of concrete materials. With the increase of the material size, the uniaxial compressive strength of the concrete specimens gradually decreased, while the corresponding strain of peak strength increased first and then decreased. The elasticity modulus fluctuated irregularly. Under the uniaxial compression conditions, five AE patterns corresponding to the deformation and failure of the concrete materials were observed. A significant nonlinear relationship was found between the AE and the stress level. The cumulative AE rings at the peak stress showed nonlinear growth with the increase of the concrete size. Based on an established relationship between the cumulative AE rings and the stress level, the necessary conditions for the existence of the quiet AE period were given. Under the uniaxial cyclic loading-unloading compression conditions, the Felicity ratio decreased first and then increased as the stress increased. The research results have some guiding significance to AE-based monitoring of internal stress evolution of coal, rock, and concrete materials and thereby enable assessment of their stability.